Multiple selves in intertemporal choice - Julian Jamison; Jon Wegener (Federal Reserve Bank of Boston, 2009)
We propose that individuals consider future versions of themselves to truly be separate persons, not simply as a convenient modeling device but in terms of actual brain systems and decision]making processes. Intertemporal choices are thus quite literally strategic interactions between multiple agents. Previous neuroscientific studies have found evidence that systems involved with Theory of Mind (that is, mentalizing other agents) are similar to those involved with prospection (imagining oneself in the future). We provide a conceptual framework for this work and suggest that, instead of prospection, a more analogous future task is one that concerns intertemporal choice and time preferences, since these involve implicit prediction of future actions. Recent functional imaging studies appear to confirm such a link. Additional studies.behavioral, clinical, and neuroimaging.are proposed in order to confirm the specific nature of the correspondence and to elucidate the underlying mechanisms. Finally, given that society may have a vested interest in promoting the welfare of future selves, we discuss possible policy implications of departing from the standard framework in which individuals act in their own best interests as defined over the entire lifetime.
Keywords: D90; D87; D62; D03; 330; intertemporal choice; theory of mind; mentalizing; intrapersonal games; neuroeconomics; Verhaltensökonomik; Zeitpräferenz; Neuroökonomie; Theorie